The Effectiveness of the Implementation of Supervision of the Regional Supervisory Council (MPD) on the Implementation of Notary Positions - Habsari, Milenia Ayu (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to determine and analyze the effectiveness of the implementation of supervision by the regional supervisory council (MPD) on the implementation of notary positions in Semarang district. The method used in this research is a qualitative approach, because problems related to humans fundamentally depend on observation. The qualitative approach is an approach where there is an event where the researcher becomes the key instrument in the research which is carried out completely on the research subject, then the results of this approach are described in the form of words written on the empirical data that has been obtained. The type of data used in this research is primary and secondary data. The type of primary data isdata in the form of information in oral form obtained directly by researchers through original sources. The primary data used is:The 1945 Constitution of the Republic of Indonesia, the Civil Code, Law Number 2 of 2004 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries.Meanwhile, secondary data is written dataSome of the secondary data used in writing this thesis include: Results of Scientific Work of Scholars, Legal Journals, Research Results of Tertiary Legal Materials: Legal Dictionaries, Encyclopedias, Print and Electronic Media. The results of the research are that at the level of correct legal rules, the Regional Supervisory Council (MPD) must place the Notary's deed as an object, because the Notary in carrying out his official duties is related to making legal documents, in the form of a deed as written evidence which is within the scope of civil law. so that placing a deed as an object must be assessed based on the legal rules relating to the making of the deed, and if it is proven that there is a violation, sanctions will be imposed as stated in Articles 84 and 85 UUJN. Keywords: Council; Effectiveness; Regional; Supervisory.